Usability Tests of Thai Mobile Banking UI Design - Inthraporn Aranyanak (My University, 2019)
Nowadays, many banking customers process their transactions via mobile banking applications because of the convenience.This study examines five well-known Thai mobile banking applications to measure their usability and compares their UI design from the perspective of nine main functions.An analytical tool for prototypes and the System Usability Scale (SUS) were used to collect and analyse data.The usability test of the five mobile banking applications in this paper involves three usability metrics: effectiveness showing the completion rate, efficiency showing the time used to successfully complete a task, and satisfaction using SUS to evaluate users' satisfaction with the product.This paper presents problems found in poor UI design and suggests how to improve mobile banking UI design.
Keywords: Usability and User Interface Design